Handbook of Philosophical Logic Volume 18 (Handbook of Philosophical Logic ;, 2018)
This eighteenth volume of the acclaimed Handbook of Philosophical Logic includes many contributors who are among the most famous leading figures of applied philosophical logic of our time. Coverage includes deontic logic, practical reasoning, homogeneous and heterogeneous logical proportion, and talmudic logic. Overall, it will appeal to students, practitioners, and researchers looking for an authoritative resource in these areas. The contributors first explore models in terms of dynamic logics for information-driven agency. The paradigm they use is dynamic-epistemic logics for knowledge and belief and their current extensions to the statics and dynamics of agents' preferences. Next, in the presentation of preference based agency, coverage examines a large number of themes, including interactive social agents and scenarios with long term patterns emerging over time. From here, the book moves on to offer an introduction to homogeneous and heterogeneous logical proportions. Readers will also learn more about the general challenge that the problem of formalizing practical reasoning presents to logical theory. The contributors survey the existing resources that might contribute to the development of such a formalization. They conclude that, while a robust, adequate logic of practical reasoning is not yet in place, the materials for developing such a logic are now available. The last chapter explores topics that deal with the logic of Jewish law and the logic of the Talmud. This includes obligations and prohibitions in Talmudic deontic logic, the handling of loops in Talmudic logic, Temporal Talmudic logic, and quantum states and disjunctive attacks in Talmudic logic. The Talmudic logic system presented are also exported to general logic and to Artificial Intelligence.